How to make a bridal bouquet: sensory knowing in action - Gåfvels, Camilla (Frontiers in Education, 2024)
This study explored the planning and making of a bridal bouquet in classroom interaction between a teacher and a student in a Swedish upper-secondary adult floristry education school. The purpose was to empirically reveal floristry disciplinary aesthetics. Aesthetics can be said to involve the exploration of sensory perception in general, entailing a focus on tacit sensory knowing. Methodologically, this study drew on the principles of ethnomethodology and (multimodal) conversation analysis to investigate videorecorded empirical data. The analysis included three separate sequences of interaction after the student requested the teacher's attention. In the sequences, the student repeatedly provided answers to her own known-answer questions, and it remained her privilege to define what should be done and why as a consequence of the teacher's authoritative guiding and gentle support. The results include examples of floristry disciplinary aesthetics in action when making a bridal bouquet, such as airiness and the role of outer shape. Moreover, in situ aesthetic judgement as part of sensory knowing is shown to be ample in the form of embodied actions, such as showing with the hands and communicating with facial expressions.